Prognostic factors of outcome in adults with non-traumatic altered mental status presenting to emergency department - Hilal Ahmad, Sheikh; Mushtaq, Wani A.; Sajad, Tak (International Journal Of Community Medicine And Public Health, 2019)
Background: Altered mental status (AMS) is a common presentation in the emergency department (ED) and poses a significant challenge to the emergency physician (EP). The prognosis seems to depend upon many diverse factors, like etiology of AMS patient, clinical variables and various laboratory tests. Methods: The aim of the study was to determine outcome in patients presenting with new onset AMS to emergency department in our population. And further to look for various prognostic factors for death. Adult patients aged >14 years, not having dementia and with no history of trauma, presenting to ED with altered mental status were included in the study. Results: Out of 200 patients, 108 were male and 92 females. Patients having AMS because of poisoning, seizure, intracranial infection all had decreased mortality. Whereas patients having AMS because of stroke, infection, cardiovascular causes had significantly increased mortality. Season, sex, pH, SaO2, TLC, GCS, mean Bp. were associated with increased mortality in patients of AMS presenting to emergency department. The logistic regression model was statistically significant (chi square=39.3, p=0.000). The model predicted 26% of the variance in predicting death and correctly classified 74.6% of patients. Conclusions: The importance of being able to prognosticate AMS patients at outset in emergency is immense.Male sex, low mean BP, low GCS, low pH, low arterial SaO2, and high TLC were predictive of higher death rate in this cohort of patients presenting to emergency department.